Challenges Facing Small and medium Tourism Enterprises around Bwindi Impenetrable National Park: A Case Study of Nkuringo Area. - Luke, Hakizimana (Kabale University, 2019)
A Research Report Submitted to the Faculty of Science in Partial Fulfillment of the Requirements for the award of the Degree of Bachelors of Tourism of Kabale University.